Joining of zirconia to Ti6Al4V using Ag-Cu sputter-coated Ti brazing filler - Simões, Sónia (2022)
The joining of zirconia (ZrO2) to Ti6Al4V using Ag-Cu sputter-coated Ti brazing filler foil was investigated. Brazing experiments were performed at 900, 950, and 980 °C for 30 min under vacuum. The microstructural features of the brazed interfaces were evaluated by optical microscopy (OM) and by scanning electron microscopy (SEM). The chemical composition of the brazed interfaces was analyzed by energy dispersive X-ray spectroscopy (EDS). Room temperature shear tests and Vickers microhardness tests performed across the interfaces were used to evaluate the mechanical strength of the joints. Multilayered interfaces were produced for all brazing temperatures, consisting essentially in α-Ti + Ti2(Ag, Cu), TiAg. Joining to ZrO2 was promoted by the formation of a hard layer, reaching a maximum of 1715 HV0.01, possibly consisting mainly in α-Ti and Ti oxide(s). Joining to the Ti6Al4V was established by a layer composed of a mixture of α-Ti and Ti2(Ag, Cu). The highest shear strength (152 ± 4 MPa) was obtained for brazing at 980 °C and fracture of joints occurred partially across the interface, throughout the hardest layers formed close to ZrO2, and partially across the ceramic sample.